Indonesia through the Lens of World Economic Forum: Global Competitive Index Analysis 2008/09-2016/17 - Nangoy, Stanley S. (11th International Scholars Conference, 2018)
This paper investigated World Economic Forum report on the trend of Indonesia competitiveness from 2008/09 to 2016/17 in order to find out factors that positively and negatively affect its long-term competitiveness sustainability. In determining the country competitiveness, World Economic Forum developed a model called Global Competitiveness Index (GCI), which classified a country economy into three stages: factor-driven, efficiency-driven and innovation-driven. Given the complex nature of competitiveness, the index identifies twelve pillars of competitiveness reflecting the diverse and interrelated factors that have a bearing on long-term potential for sustained growth and prosperity. Data published by World Economic Forum from 2008/09 to 2016/17 were collected and analyzed in form of competitive scores and ranks. The result showed that in 2016, Indonesia’s competitiveness ranks 41st among 138 countries with competitive status at efficiency driven economy, ranks 4th among ASEAN countries behind Singapore, Malaysia and Thailand. Corruption, inefficient government bureaucracy and inadequate supply of infrastructure are three most problematic factors must be addressed to ensure Indonesia competitiveness regionally and globally.